First record of the brown mussel (Perna perna) from the European Atlantic coast - Lourenço, Carla R. (2014)
The occurrence of the brown mussel Perna perna is reported for the first time from the European Atlantic coast, on the southern Portuguese coast. Several specimens of this mytilidae species were identified in exposed rocky intertidal habitats in Vilamoura (37804019.7000N 8807019.7100W) and Ilha do Farol (36858029.3800N 7851042.5100W). It is suggested that, under warming climate conditions, this subtropical/tropical species might have extended its geographical distribution from North Africa.